Assessment of medication-related liver and kidney impairment in admitted patients in Depok, Indonesia: an observational study employing the Naranjo algorithm - Syafhan, Nadia Farhanah; Aldora, Ghea Shafa; Kamila, Shinta (Universitas Ahmad Dahlan, 2025)
Liver and kidney impairment caused by medications represents serious side effects that may extend hospital stays and increase the risk of patient death. Implementing strategies to recognize, document, and analyze cases of patient harm related to drug use is crucial for medicines optimization. This study aimed to evaluate the prevalence of medication-related liver and kidney impairment among hospitalized patients, while also identifying the specific medication categories implicated. A retrospective review of patient records was conducted at Universitas Indonesia Hospital (Depok, Indonesia), focusing on adult patients diagnosed with liver or kidney impairment during their 2021 hospital admission. The Naranjo algorithm was applied to assess the likelihood that these injuries were caused by medications. Among the 4,273 admitted patients, it was found that 1.01% experienced medication-related liver impairment (MRLI), while 0.77% experienced medication-related kidney impairment (MRKI). The most common medications associated with liver impairment were antibiotics (31.58%), cardiovascular medications (24.21%), pain relievers (14.74%), anti-ulcer medications (11.58%), antiviral medications (8.42%), antiemetics (8.42%), and antidiabetic medications (1.05%). In contrast, kidney disease was primarily linked to diuretics (29.76%), antibiotics (21.43%), ACE inhibitors/ARBs (21.43%), antiviral medications (9.52%), and NSAIDs (7.14%). Importantly, there was no statistically significant correlation between the occurrence of MRLI or MRKI and factors such as gender, age, body mass index (BMI), or the presence of other health conditions (p > 0.05). These findings underscore the need for heightened awareness regarding the potential for medication-related impairments in hospitalized patients and suggest that careful monitoring of medication use is essential to mitigate these risks.